The Influence of Social Trust, Income Inequality, and Employment Status on the Risk of Depression - Dhina Nur Irfani; Bhisma Murti; Yulia Lanti Retno Dewi; Revi Gama Hatta Novika; Ika Sumiyarsi Sukamto (Masters Program in Public Health, 2025)
Background: Depressive disorders are among the most common and complex mental health problems worldwide, including in Indonesia. The determinants of depression are closely linked to social and economic factors. This study aimed to estimate the effects of social trust, income inequality, and employment status on the risk of depression. Subjects and Method: An observational study with a cross-sectional design utilized the fifth wave of the Indonesia Family Life Survey (IFLS5). The dataset includes more than 29,716 individuals across 13 provinces. The sample was selected using a purposive sampling method. Results: The risk of depression increased significantly among individuals who were unmarried (b = 0.97; 95% CI: 0.84 to 1.07; p < 0.001), female (b = 0.16; 95% CI: 0.06 to 0.26; p = 0.002), unemployed (b = 0.25; 95% CI: 0.14 to 0.35; p < 0.001), and living in provinces with higher income inequality (b = 0.32; 95% CI: 0.21 to 0.42; p < 0.001). Conversely, the risk of depression decreased significantly with higher social trust (b = -0.18; 95% CI: -0.29 to -0.08; p < 0.001), good sleep quality (b = -0.20; 95% CI: -0.21 to -0.19; p < 0.001), older age (b= -0.81; 95% CI: -0.99 to -0.63; p < 0.001), and higher education level (≥senior high school) (b= -0.36; 95% CI: -0.46 to -0.25; p < 0.001). Conclusion: The risk of depression increases with unmarried, female, unemployed, and living in provinces with higher income inequality. The risk of depression decreases with higher social trust, good sleep quality, older age, and education ≥senior high school.